2016
DOI: 10.1111/echo.13358
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic correlates of severe pulmonary hypertension in adult patients with ostium secundum atrial septal defect

Abstract: Larger size of ASD using the QP/QS ratio and increased right-sided tricuspid E/e' ratio correlated with severe PH with a sPAP of 70 mm Hg or more. Patients with severe PH had more severe RV dysfunction as evaluated by TAPSE and RVFSA in comparison to those with PH <70 mm Hg. LV diastolic function was also reduced in the severe PH group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Consistent with past studies, we observed that PH patients had a higher burden of baseline comorbidities than patients without PH. 10,18,30,34,35 Given the scarcity of literature, existing studies are heterogenous in reporting long-term outcomes in this population. Although adverse events were rare, higher rates were observed in patients with PH 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with past studies, we observed that PH patients had a higher burden of baseline comorbidities than patients without PH. 10,18,30,34,35 Given the scarcity of literature, existing studies are heterogenous in reporting long-term outcomes in this population. Although adverse events were rare, higher rates were observed in patients with PH 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and diagnostic characteristics supported distinct hemodynamic properties between groups whom similar to other studies though no difference in size defect was found between groups. Conflicting findings in other studies exist regarding PH severity and defect size ( 16 , 17 ). Determination of defect size in available studies was done using echocardiography where the accuracy of the results depends on the view taken, the form of ASD, as well as individual expertise.…”
Section: Discussionmentioning
confidence: 70%
“…However, in large defects (>1.5 cm) all develop the syndrome in time, if there is no intervention. For ASDs, a recent publication demonstrates the same finding, that defects most likely to have severe PAH were the largest (31.84 ± 8.21 mm) [ 12 ]. More complex lesions such as atrioventricular septal defects or truncus arteriosus often develop PAH early in life.…”
Section: Causes and Pathophysiologymentioning
confidence: 82%